Pyrogenic Carbon Generation From Fire and Forest Restoration Treatments - DeLuca, Thomas H.; Gundale, Michael J.; Brimmer, Rachel J.; Gao, Si (Frontiers in Forests and Global Change, 2020)
Pyrogenic carbon (PyC) is a chemically stable form of carbon (C) generated during fire events and is one of the few legacies of fire recorded in soil; however, the significance of this material as a form of C storage in forest ecosystems has received only limited scientific attention, and currently relatively little is known regarding the quantity of PyC generated during forest restoration efforts that include prescribed (Rx) fire. Quantifying the rate of PyC production during fire events is essential to estimating the potential for ecosystem C storage in forest systems where wildfire is a common natural disturbance and Rx fire is used as a fuel management practice. In this paper, we report on the average mass of PyC formation during wildfire and Rx fire events in forest ecosystems through synthesizing data across 12 published studies; and we report empirical data on the mass of PyC generated in a replicated Rx fire study in a ponderosa pine (Pinus ponderosa) forest ecosystem of the Rocky Mountain West. Our data synthesis showed that PyC (consisting of PyC from downed wood, O horizon, and mineral soil) was, on average, produced at a rate of 5.2% of biomass exposed to fire in forest ecosystems, and a single wildfire or Rx fire event generated about 2.2 Mg C ha-1 in the form of PyC. In our empirical study, we collected O horizon and surface mineral soil (0 – 10 cm) samples from the Fire and Fire Surrogates study plots in western Montana (treatments: control, thin, burn, thin&burn) that was burned in 2002 and analyzed for PyC content using a wet digestion method. The two Rx fire treatments had significantly higher PyC contents in the O horizon compared to the control. In the thin&burn treatment, PyC was formed at a rate of about 12% of total biomass consumed yielding approximately 2.24 Mg PyC C ha-1 in the O horizon. Mineral soil PyC contents were not affected by Rx fire. Wildfire and Rx fires generate a substantial amount of PyC which initially resides in the O horizon and serves as a stable form of ecosystem C.